Income Inequality and Economic Growth: Application of Quantile Regression - Sbaouelgi, Jihène (Asian Development Policy Review, 2017)
The main objective of this article is to examine the relationship between the income inequality and the economic growth using quantile regressions. This methodology takes into account the heterogeneity of the parameters through the conditional distribution of the sample growth. In fact, the impact of the income inequality on the economic growth differs from one income group to another through different transmission channels such as the financial liberalization, the commercial liberalization, the corruption, the human capital and the political stability. According to the results, the income inequality exerts low impact on the growth through the trade openness.